Comparison of respiratory morbidity in late preterm infants and intrauterine growth retarded infants at school-age - US, MAHMUT CANER (My University, 2022)
Objective: We aimed to determine respiratory morbidity of late preterm infants versus infants with intrauterine growth retardation (IUGR) at school-age. Patients and Methods: Late preterm appropriate for gestational age (AGA) infants (34-36, 6/7 weeks) (Group 1), IUGR infants (Group 2), extremely preterm AGA (Group 3) and term AGA infants (Group 4) born between 2004 and 2008 were included in this casecontrol study and assessed for respiratory morbidity at school-age. We evaluated the impact of late preterm compared with IUGR and term gestation on respiratory morbidity by using validated American Thoracic Society – Division of Lung Diseases (ATS-DLD-78-C) and the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaires. Questionnaires on wheezing, infectious respiratory morbidity, and physician-diagnosed asthma panels were constituted and groups were compared. Results: A total of 160 patients were enrolled in the study and 97 (60.6%) of them were boys. Respiratory morbidities at schoolage were found to be significantly higher in both late preterm and IUGR groups when compared to term controls. Each weekly increase in gestational age reduced the risk for wheezing episodes (OR perGW:0.82,95%CI:0.71-0.97, p:0.02). Regarding infectious respiratory morbidities, there was a significant increase when the number of people living at home increased (OR perperson:1.79,95%CI:1.12-2.87, p:0.01), and a decrease in female gender (OR:0.41,95%CI:0.17-0.99, p:0.04) and in the week of gestation (OR perGW:0.84,95%CI:0.71-1.00, p:0.04). Atopic dermatitis (OR:5.26,95%CI:1.57-17.69, p<0.01) and maternal asthma (OR:5.38,95%CI:1.17-24.60, p:0.03) history were found to be risk factors for asthma. Conclusion: Being IUGR may be an important risk factor for respiratory morbidity at school-age. Further studies are needed on this subject.
Keywords: Premature Birth; Late preterm; Fetal Growth Retardation; Asthma; School-age